Optimizing ISO 9001: 2015 Implementation with Swot and QSPM Method - Pratiwi, Chega Putri; Gunarto, Muji (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 1 Tahun 2021DO - 10.24843/MATRIK:JMBK.2021.v15.i01.p12, 2021)
PT Saba Indomedika Jaya obtained results that indicate an indication of strategic initiatives that are still ineffective to be implemented in supporting the success of the process and requirements of the ISO 9001: 2015 clause in the 2018 and 2019 audits. Therefore, it is necessary to identify alternative strategies and determine priority strategies to optimize ISO 9001: 2015 at PT Saba Indomedika Jaya. The research method used is the descriptive qualitative method using SWOT analysis tools (Strengths, Weaknesses, Opportunities, and Threats) and QSPM (Quantitative Strategic Planning Matrix). There were 12 alternative strategies to optimize the ISO 9001: 2015 quality management system using the SWOT matrix (Strengths, Weaknesses, Opportunities, Threats). After going through three stages of strategic management planning that uses QSPM (Quantitative Strategic Planning Matrix) as a tool for selecting the main alternative strategy, the main strategy is obtained, which has the highest attractiveness value of 5.6619, namely creating a competency matrix and conducting training to reduce competency gaps. between employees .